2015
DOI: 10.1128/jb.02496-14
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of Streptococcus mutans Persisters Induced by the Quorum-Sensing Peptide Pheromone Is Affected by the LexA Regulator

Abstract: bThe presence of multidrug-tolerant persister cells within microbial populations has been implicated in the resiliency of bacterial survival against antibiotic treatments and is a major contributing factor in chronic infections. The mechanisms by which these phenotypic variants are formed have been linked to stress response pathways in various bacterial species, but many of these mechanisms remain unclear. We have previously shown that in the cariogenic organism Streptococcus mutans, the quorumsensing peptide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 66 publications
3
33
0
Order By: Relevance
“…20 However, this stress-inducible persistence phenotype was abolished in any quorum sensing-deficient mutants. 20,23 This confirmed the importance of quorum sensing signaling in mounting an adaptive stress response within a subpopulation of S. mutans to form persisters for survival of the species. We previously identified the CSP regulon of S. mutans 21 and found that a novel putative tripartite type II TA system, named SmuATR, was up-regulated under CSP conditions.…”
Section: Introductionsupporting
confidence: 55%
See 2 more Smart Citations
“…20 However, this stress-inducible persistence phenotype was abolished in any quorum sensing-deficient mutants. 20,23 This confirmed the importance of quorum sensing signaling in mounting an adaptive stress response within a subpopulation of S. mutans to form persisters for survival of the species. We previously identified the CSP regulon of S. mutans 21 and found that a novel putative tripartite type II TA system, named SmuATR, was up-regulated under CSP conditions.…”
Section: Introductionsupporting
confidence: 55%
“…It was demonstrated that different stresses encountered in the oral cavity increased the level of persisters . However, this stress‐inducible persistence phenotype was abolished in any quorum sensing‐deficient mutants . This confirmed the importance of quorum sensing signaling in mounting an adaptive stress response within a subpopulation of S. mutans to form persisters for survival of the species.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…For MS, the stress-dependent QS system is primarily comprised of the CSP and its ComD/ComE 2-component signal transduction system for communication between biofilm cells of the same species, while interspecies signalling is mediated via the autoinducer-2 molecule produced by LuxS [Senadheera and Cvitkovitch, 2008]. The CSP-mediated QS system in S. mutans affects biofilm formation, acidogenicity, aciduricity, genetic transformation, bacteriocin production, stress response, and the ability to produce persister phenotypes [Leung et al, 2015]. Targeting QS signalling pathways could provide a promising avenue in the development of novel therapeutics to alter cariogenic biofilms.…”
Section: Quorum-sensing Targetsmentioning
confidence: 99%
“…Also, ATP depletion is associated with persister formation in S. aureus (22). LexA, a DNA-binding protein that represses the SOS response in bacteria, is involved in the formation of Streptococcus mutans persisters induced by the competence-stimulating peptide (CSP) (26). Lastly, Streptococcus pneumoniae (pneumococcus) exhibits phenotypic tolerance to vancomycin and penicillin in a capsuledependent fashion (27), and this tolerance is epigenetically inherited by daughter cells (28).…”
mentioning
confidence: 99%